Directed energy deposition GRCop-42 copper alloy: Characterization and size effects. (October 2022) - Demeneghi, Gabriel; Barnes, Baxter; Gradl, Paul; Ellis, David; Mayeur, Jason R.; Hazeli, Kavan
Graphical abstract: Highlights: Surface topography, porosity, and texture are independent of the wall thickness. Surface topography influences the mechanical behavior of thin specimens more readily. While specimens are highly textured, no anisotropic mechanical response is observed. Mechanical response of unpolished specimens is highly dependent on build orientation. Abstract: Laser Powder Direct Energy Deposition (LP-DED) allows for manufacturing of large components while still maintaining internal thin walls for heat exchanger applications. The LP-DED process has been matured for alloys including stainless steels, superalloys, and titanium, but has had very limited research using copper-based alloys, which are important for applications that require high thermal conductivity. This study quantifies the size effects on microstructure, surface metrology, microhardness, and mechanical response to tensile loads for different thicknesses and powder compositions of hot isostatic pressed (HIP) LP-DED Copper-Chromium-Niobium alloy, specifically GRCop-42. To accomplish this, tensile specimens were sectioned from single track build walls in both horizontal and vertical orientations to also investigate possible anisotropic behavior in the part. Results show that microstructure, hardness, surface metrology, and porosity are independent of wall thickness. Uniaxial loading response showed some variations with specimens orientation and size effects. For vertical specimens, thicker specimens showed a 6% higher elongation than thinner specimens. Horizontal specimens showed close to double the elongation when compared to vertical specimens, where thinner specimens had a higher reduction in elongation than thicker specimens. Additionally, removing the surface effects through polishing practically eliminated the anisotropic behavior between horizontal and vertical specimens along with the observed size effects. To demonstrate size effects dependency on the manufacturing process comparison is made between GRCop-42 alloy produced by Laser Powder Bed Fusion (L-PBF) and LP-DED.